1995
DOI: 10.1159/000227459
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of CYFRA 21-1 in Malignant Pleural Fluids

Abstract: The diagnostic value of the novel tumor marker CYFRA 21-1 in malignant pleural fluid was assessed in comparison to carcinoembryonic antigen (CEA). CYFRA 21-1 and CEA were measured in pleural fluid obtained from patients with 108 malignant and benign diseases. The levels of pleural fluid CYFRA 21-1 in malignant diseases (median: 84.5 ng/ml) were statistically higher than those in benign diseases (median: 13.9 ng/ml; p < 0.01). The CYFRA 21-1 test was able to discriminate significantly between squamous cell lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
3
10
0
3
Order By: Relevance
“…On the other hand, Romero et al (1996) observed a sensitivity of only 38% for CYFRA, in a small series of 41 malignant effusions. Thus, our results agree with those of Satoh et al (1995) and Toumbis et al (1996), and we confirm that CYFRA is one of the most efficient tumour markers available for the diagnosis of malignant effusions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, Romero et al (1996) observed a sensitivity of only 38% for CYFRA, in a small series of 41 malignant effusions. Thus, our results agree with those of Satoh et al (1995) and Toumbis et al (1996), and we confirm that CYFRA is one of the most efficient tumour markers available for the diagnosis of malignant effusions.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, when we only considered the group of carcinomas and mesotheliomas, the sensitivity of CEA and CYFRA appeared to be significantly higher (64.7% and 58.8% respectively), reaching the levels of sensitivity previously described for various tumour markers, such as CEA, CA 72-4 or CA 15-3 (Ferroni et al, 1990;Rapellino et al, 1990;Villena et al, 1996). Satoh et al (1995) and Toumbis et al (1996) described similar results for CYFRA, but Satoh reported a higher sensitivity for CYFRA than for CEA. On the other hand, Romero et al (1996) observed a sensitivity of only 38% for CYFRA, in a small series of 41 malignant effusions.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, compared to CEA and CA 72-4, CA 15-3 showed an atypical pattern in mesotheliomas, with a sensitivity of 45.5%, in agreement with the results of Villena et al (1996). The data published for pleural CYFRA are more controversial, notably concerning the thresholds and the overall sensitivity which is described as either higher (Satoh et al, 1995) or lower than the sensitivity of CEA (Romero et al, 1996). Confirming our prior study (Salama et al, 1998), we observed similar sensitivities for pleural CEA and pleural CYFRA but above all, a high sensitivity for pleural CYFRA in mesotheliomas.…”
Section: Discussionsupporting
confidence: 78%
“…An accurate diagnosis can be madeif the cytologic, histologic, or bacteriologic results are positive. Various biomarkers in the pleural effusion have been investigated to distinguish malignant effusions from benign (1)(2)(3)(4)(5). However, their usefulness in the diagnosis of pleural effusions has not been fully established.…”
Section: Introductionmentioning
confidence: 99%